EFFECT OF WORK ENVIRONMENT AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE IN PT. NESINAK INDUSTRIES - Badrianto, Yuan; Ekhsan, Muhamad (STIE Kusuma Negara, 2020)
Improving employee performance is one of the main factors for companies to achieve goals. In addition to being a factor in achieving goals, employee performance is also a way to measure the quality of human resources in a company. Some factors that can influence the success of employee performance include the work environment and job satisfaction. The purpose of this study is to find out whether there is an influence of the work environment and job satisfaction variables on employee performance. This study is to examine the effect of work environment and job satisfaction on employee performance at PT. Nesinak Industries. The company is engaged in manufacturing automotive and electronic spare parts made from rubber. The sample in this study amounted to 88 respondents who worked in the production department. This research uses quantitative methods. Data for conducting this research was obtained through filling out questionnaires by predetermined respondents. Data analysis method used is multiple linear regression analysis method. Based on the results of the t test (partial) and f test (simultaneous) of this study, showed that the variable work environment and job satisfaction bring a positive and significant effect on employee performance partially and simultaneously.